Carbonate dissolution and replacement by odinite and saponite in the Lafayette nakhlite: Part of the CO2-CH4 cycle on Mars?. (1st June 2022) - Piercy, J.D.; Bridges, J.C.; Hicks, L.J.
Highlights: Ca-siderite comprises between trace amounts and 4% of Lafayette sections. Electron Microscopy and synchrotron analysis shows variable carbonate dissolution. Ferric-(hydr)oxide nanoparticles are present on saponite and corroded siderite. Serpentine-berthierine is re-described as odinite, a ferric low-temperature mineral. Dissolution of carbonate can lead to methane on Mars via a Sabatier type reaction. Abstract: New mineralogical studies of Lafayette reveal that it contains a notably variable abundance of martian carbonate. Four percent was identified in mesostasis (3.2%) and olivine-hosted (0.8%) fractures in one polished section, but only 0.2% of both textural types in another. The Lafayette carbonates are Mg0.0-2.0 Cc13.2-38.6 Sd17.7-81.9 Rh3.1-42.9 . They have undergone variable but extensive amounts of dissolution and replacement as the nakhlite secondary fluid evolved, associated with the precipitation of ferric saponite in olivine fractures and a serpentine-like phyllosilicate in the mesostasis. The mesostasis carbonate has undergone the highest degree of corrosion and replacement. TEM analysis has shown the presence of Fe-(hydr)oxide (likely ferrihydrite) nanoparticles on olivine-hosted carbonates which can be linked to the cessation of more extensive carbonate dissolution at those sites. The mesostasis serpentine-like mineral has been described here on the basis of WDS and EDX analyses, HRTEM and Fe-K XANES, as odinite, a ferric, 0.7 nm d001 -spacings phyllosilicate mineral with a characteristic 1:1 serpentine-like structure. The carbonate dissolution stage and then formation of Fe-(hydr)oxide nanoparticles occurred under circumneutral-alkaline conditions (7) < pH < 10. This range of pH is also where the general dissolution mechanism switched from a proton-promoted, to a water hydrolysis reaction associated with a reduction in the dissolution rates. As dissolution rates were reduced and the fluid had cooled to ≤50 °C, the precipitation of the ferric saponite and odinite, a phyllosilicate associated with temperatures of ∼25 °C, dominated over the carbonate dissolution. The extensive dissolution of such crustal carbonate across the upper martian crust, producing bicarbonate and carbon dioxide, and the coupled formation of ferric phyllosilicates, would lead to the formation of CH4 in substantial amounts via a Fischer-Tropsch type reaction. The results of our study illustrate a process to explain the relatively low abundance of detected carbonate on Mars and a likely source for some of the methane on Mars.